Pengaruh Kepemimpinan terhadap Kinerja Karyawan dan Hasil Produksi pada PT. Seidensticker Indonesia (Lembaga Pengembangan Kinerja Dosen, 2023)
Human resources are the most valuable asset in a company, as they play a key role in its sustainability. Every organizational action and plan is carried out by individuals united to achieve common goals. Therefore, companies need high-quality employees and effective leadership to monitor performance and meet objectives. This study applies a qualitative approach, which is a natural, holistic method that focuses on meaning, understanding, concepts, symbols, and characteristics through descriptive narratives. The goal is to gain a deeper understanding of specific phenomena. One critical factor influencing employee performance is leadership, which includes the ability of managers and leadership teams to provide motivation, guidance, and work support. Leaders must communicate effectively so that information is clearly conveyed and accepted by subordinates. Good communication prevents misunderstandings and supports goal achievement. At PT Seidensticker Indonesia, effective leadership improves team performance and adaptability. Listening to team input and delivering clear direction are essential for building productive and harmonious workplace relationships. Leadership quality directly contributes to employee motivation and company success.